Influence of aging on transformation characteristics in shape memory CuZnAl alloys - Kayali, N; Zengin, R; Adigüzel, O (Minerals Metals Materials Soc, 2000)
Shape memory alloys exhibit superelasticity when they are deformed in a temperature range where the thermoelastic martensite forms on application of a strain. The martensite persists upon removal of the applied strain, and the alloy recovers the original shape on heating over the reverse-transformation temperature after removing the strain. The beta-phase CuZnAl alloys have beta-type superlattice in the parent case, and M9R or M18R martensites occur on quenching the alloys from the homogenization temperature. The basal plane of martensite is exposed to hexagonal distortion with martensitic transformation as well as the monoclinic distortion in the crystal structure, and splittings are observed in some selected diffraction-peak pairs due to the differences in atom sizes in lattice points. These pairs have a great importance as ordering criteria and satisfy a special relation between Miller indices. The present text reports the variation of the differences in interplane spacings (Delta d) between some selected planes upon the further aging at room temperature at which alloys are fully martensitic. The decrease of Delta d during the aging implies that the monoclinic distortion decreases. The mass increases are caused by the oxidation upon heating the alloys at high temperatures close to the betatizing temperature at free atmosphere.
Keywords: Zn-Al-Alloys; Long-Range Order; Martensitic-Transformation; 18R-Type Martensite; Ni Alloys; Cu; Stabilization; Temperature; Morphology; Additions